PENGARUH BEBAN KERJA, KOMUNIKASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU - Ni Luh Ina Handariani; I Nengah Suarmanayasa; Ni Made Ary Widiastini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine and analyze several influences, namely: (1) workload, communication and job satisfaction; (2) workload; (3) communication; and (4) job satisfaction on teacher performance at SMP Negeri 8 Singaraja. The population in this study were all 44 teachers at SMP Negeri 8 Singaraja. This research is included in the category of causal research using a quantitative approach. Data collection in this study was carried out by survey using a questionnaire. The data analysis method used is multiple linear regression analysis. The results of the study show that: (1) workload, communication and job satisfaction have a significant effect on teacher performance at SMP Negeri 8 Singaraja; (2) workload has no effect on teacher performance at SMP Negeri 8 Singaraja; (3) Communication has a positive and significant effect on teacher performance at SMP Negeri 8 Singaraja; (4) Job satisfaction has no effect on teacher performance at SMP Negeri 8 Singaraja.